Sobre una conjetura de De Giorgi para problemas elípticos en Rn /On a conjecture of De Giorgi for elliptical problems in Rn (2009)
En este trabajo se estudian las demostraciones de la conjetura de De Giorgi para dimensiones dos y tres. Se incluye una prueba para una versión más general de la conjetura que la formulada por De Giorgi en dichas dimensiones. En el transcurso del trabajo probaremos resultados que por sí solos son muy importantes en la teoría elíptica de ecuaciones diferenciales parciales de segundo orden. / Abstract. In this work we study the demonstrations of the De Giorgi conjecture for dimensions two and three. It is include a proof for a more general version of the conjecture than the one enounced for De Giorgi in these dimensions. During the development of the work will been proved some results that are important itself in the elliptic theory of partials differential equations of second order.